Security or autonomy?: a comparative analysis of work values and labor market policies in different European welfare states - Weiß, Julia; Hörisch, Felix (International journal of social welfare, 2022)
This paper analyzes whether and how work values differ between European Welfare states and change over time. We proceed in three steps: First, we show that—despite EU harmonization endeavors, for example, via the Europe 2020 strategy—work values still vary substantially between European countries and welfare regimes. Second, by analyzing data from the European Social Survey 2004 and 2010, we show how labor market policies, such as active and passive labor market policies, are associated with work values and how overall levels of work values changed over this period. Third, we discuss potential implications of the heterogeneity of work values for national as well as European labor market policy making. Altogether we are able to show that work values are substantially driven by the economic structure of a country and its labor market policy making. Key Practitioner Message Work values vary substantially between European countries and welfare regimes. The change of work values is substantially driven by welfare state structures (both labor market policies implemented and industry share). Both European and national labor market policy making has to account for these different work values to be successful.